2001
DOI: 10.1038/sj.ijo.0801485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening of the proopiomelanocortin (POMC ) gene in Italian obese children: report of three new mutations

Abstract: Mutations in codons 7 and 9 of the signal peptide may alter the translocation of the pre-proopiomelanocortin into the endoplasmic reticulum and, therefore, can be implicated in obesity. Although further studies are required, the polymorphism between position 6997 and 6998 may represent one of the genetic variations that explain the linkage between obesity and POMC. International Journal of Obesity (2001) 25, 61-67

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 28 publications
3
27
1
Order By: Relevance
“…In a French study, R236G was present in 1.65% (3 of 182) of individuals (mean BMI Ͼ31.8 kg/m 2 ) in association with early-onset obesity and in 1.04% of controls (8 ). R236G was also detected in 1.15% (1 of 87) of obese Italian children (BMI standard deviation score ϭ 3.43) (9 ). Interestingly, it was also identified in 0.6% (1 of 156) of individuals in a Danish study of juvenile-onset obesity (BMI ϭ 35.8 kg/m 2 ) diagnosed when the individual was ϳ20 years of age (7 ), which coincides with our heterozygous carrier of this variant, a female diagnosed as obese at 21 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In a French study, R236G was present in 1.65% (3 of 182) of individuals (mean BMI Ͼ31.8 kg/m 2 ) in association with early-onset obesity and in 1.04% of controls (8 ). R236G was also detected in 1.15% (1 of 87) of obese Italian children (BMI standard deviation score ϭ 3.43) (9 ). Interestingly, it was also identified in 0.6% (1 of 156) of individuals in a Danish study of juvenile-onset obesity (BMI ϭ 35.8 kg/m 2 ) diagnosed when the individual was ϳ20 years of age (7 ), which coincides with our heterozygous carrier of this variant, a female diagnosed as obese at 21 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to nonsyndromic obesity, four mutation screening studies involving 601 nonsyndromic obese subjects have shown missense or nonsense mutations in just 7 individuals, implying that coding sequence variation in POMC is a very uncommon cause of nonsyndromic obesity (15)(16)(17)(18). Two genome-screening studies, in French obese sibling pairs and in Mexican-American ex- tended families, suggested strong evidence for linkage of plasma leptin levels to the region of chromosome 2 harboring the POMC gene (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…15 Polymerase chain reaction (PCR) products were screened using the single-strand conformation polymorphism (SSCP) analysis as previously described. 19 Subsequently, MC4R amplification was repeated using the same primer pairs in a buffer containing 20 mM Tris -HEPES, 10 mM KCl, 10 mM ammonium sulfate, 2 mM MgCl 2 and the Amplitaq Gold DNA polymerase (Perkin Elmer, USA). PCR products (3 ml) were analysed by a Wave (Transgenomic, USA) denaturing high-performance liquid chromatography (DHPLC) system.…”
Section: Methodsmentioning
confidence: 99%